IDENTIFIKASI SPESIES UDANG MANTIS (Stomatopoda) DI PERAIRAN PEMUTERAN DENGAN MENGGUNAKAN GEN CYTOCHROME C OXIDASE SUBUNIT-1 DARI DNA MITOKONDRIA - OKA PUJAWAN, ANAK AGUNG NGURAH; KADE MAHARDIKA, I GUSTI NGURAH; SARI NINDHIA, TJOK (Faculty of Veterinary Medicine, Udayana University, 2012)
Mantis shrimp is known as a bio-indicator of marine ecosystem health. Pemuteran is one of the waters in Indonesia that has a wealth of interesting marine life. Knowledge of the genetic structure was used for identification of species of mantis shrimp. The purpose of this study was to identify species of mantis shrimp in the waters of Pemuteran and determine their relationship with mantis shrimp in other areas of Indonesia around the world.The method used in this research was the polymerase chain reaction technique (PCR) of the molecular of marker Cytochrome c oxidase subunit 1 from mitochondrial DNA. The sample was mantis shrimps in the form of adult and larvae, that were collected in Pemuteran. The number of samples was 32. Sequence from each sample was determined by cycle sequencing technique and analyzed at Cornell University. Sequences obtained in this study and that downloaded from GeneBank were analyzed with MEGA5.3.The results showed that four species of mantis shrimp, i.e. Haptosquilla glyptocercus, Gonodactyllelus annularis, Gonodactylus viridis and Chorisquilla Hystrix, could be identified. Genetic relationship of mantis shrimp in Pemuteran to that of various regions varies. Close relationship was found to the mantis shrimp species in the Coral Triangle region. The species were genetically in a further distance to the mantis shrimp found in other areas, such as Australia's east coast. Determination of species from specimens that are close to Gonodactylus viridis and Chorisquilla Hystrix is necessary to justify whether the specimens are properly included to the corresponding species or they should be assigned as new species